Meminimalkan Risiko dan Maksimalkan Keuntungan: Strategi Manajemen Risiko dalam Pengelolaan Wakaf Produktif - Agil, Muhammad; Sholikhah, Noviana Nur; Zunaidi, Arif; Ahmada, Milla (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
This research discusses risk management strategies for managing productive waqf with the aim of minimizing risks and maximizing profits. This research uses a literature analysis method by prioritizing descriptive and qualitative methods. The research results show that risk identification, evaluation, and control are key stages in productive waqf risk management. Risk control strategies such as investment diversification, the use of derivative financial instruments, and creating contingency plans have proven effective in managing risk. Continuous evaluation and monitoring are also important to ensure risk control strategies remain relevant and effective. In conclusion, risk management is a key element in maintaining the sustainability of productive waqf programs. By implementing appropriate risk management strategies, waqf managers can minimize potential losses and ensure that waqf assets remain productive and provide sustainable benefits to society.